2021
DOI: 10.21037/tau-21-703
|View full text |Cite
|
Sign up to set email alerts
|

Heparin modification improves the re-endothelialization and angiogenesis of decellularized kidney scaffolds through antithrombosis and anti-inflammation in vivo

Abstract: Background: Constructing tissue-engineered kidneys using decellularized kidney scaffolds (DKS) has attracted widespread attention as it is expected to be the key to solving the shortage of donor kidneys.However, thrombosis and the host inflammatory response are unfavorable factors that hider the reendothelialization and vascularization of the decellularized scaffolds.Methods: Heparin was immobilized into the DKS using the method of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide/N-hydroxysuccinimide (EDC/NHS) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…As mentioned earlier, endothelial cells were confirmed to attach to a heparin-modified material surface [ 11 , 12 , 13 , 17 ], which was also found in our current result. The results also showed that the endothelialization effect on the heparinized scaffolds was not comparable to the un-modified one, which might raise a contradiction on the initial purpose of employing heparin on the bovine pericardial scaffolds.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As mentioned earlier, endothelial cells were confirmed to attach to a heparin-modified material surface [ 11 , 12 , 13 , 17 ], which was also found in our current result. The results also showed that the endothelialization effect on the heparinized scaffolds was not comparable to the un-modified one, which might raise a contradiction on the initial purpose of employing heparin on the bovine pericardial scaffolds.…”
Section: Discussionsupporting
confidence: 90%
“…Endothelial cells were shown not to express direct receptors for heparin. The positive effects of the heparin immobilized scaffold on endothelial cells were described via “bridging” molecules, e.g., chitosan, gelatin [ 11 , 17 ], or binding and stabilizing cell growth factors, e.g., VEGF [ 12 , 13 ]. Therefore, the decrease in cell adherence or proliferation on HepBPS could be explainable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b shows the FTIR spectrum of LMWH and OL, it was found that both of them had characteristic absorption peaks at 892 cm −1 and 936 cm −1 . 23,24 The C–O–S stretching vibration absorption peak of the sulfuric acid group on amino hexose appeared around 830 cm −1 , the strong absorption peak of O–S stretching vibration appeared around 1240 cm −1 , and the C O stretching vibration peak of the sulfuric acid group in the carboxyl group appeared around 1621 cm −1 was also found in both, all of these indicated that the main structure of the OL obtained after oxidation did not change significantly. It has been known that the reason for the conspicuous anticoagulant activity and cytocompatibility of LMWH is the presence of a reactive pentose structure in its molecular chain, 25 they can bind to antithrombin III (AT III), change the conformation of the antithrombin molecules, and inhibit the activity of coagulation factors IIa, Xa and IXa, exhibiting strong anticoagulant properties.…”
Section: Resultsmentioning
confidence: 99%
“…It binds to many growth factors such as Transforming Growth Factor (TGF), VEGF and Fibroblast Growth Factor (FGF) [ 14 , 18 ]. It is widely used due to its anti-inflammatory and other pharmacological properties [ 19 ]. It binds to a wide number of proteins and helps in regulating their function [ 20 ].…”
Section: Introductionmentioning
confidence: 99%